Phase‐Modulated Interferometry, Spectroscopy, and Refractometry using Entangled Photon Pairs. Issue 11 (22nd January 2020) - Lavoie, Jonathan; Landes, Tiemo; Tamimi, Amr; Smith, Brian J.; Marcus, Andrew H.; Raymer, Michael G.
Abstract: The authors demonstrate a form of two‐photon‐counting interferometry by measuring the coincidence counts between single‐photon‐counting detectors at an output port of a Mach–Zehnder Interferometer (MZI) following injection of broad‐band time‐frequency‐entangled photon pairs (EPP) generated from collinear spontaneous parametric down conversion into a single input port. Spectroscopy and refractometry are performed on a sample inserted in one internal path of the MZI by scanning the other path in length, which acquires phase and amplitude information about the sample's linear response. Phase modulation and lock‐in detection are introduced to increase detection signal‐to‐noise ratio and implement a "down‐sampling" technique for scanning the interferometer delay, which reduces the sampling requirements needed to reproduce fully the temporal interference pattern. The phase‐modulation technique also allows the contributions of various quantum‐state pathways leading to the final detection outcomes to be extracted individually. Feynman diagrams frequently used in the context of molecular spectroscopy are used to describe the interferences resulting from the coherence properties of time‐frequency EPPs passing through the MZI. These results are an important step toward the implementation of a proposed method for molecular spectroscopy—quantum‐light‐enhanced 2D spectroscopy. Abstract : To advance the field of quantum‐light‐enhanced spectroscopy, the authors demonstrate a new form of two‐photon‐counting interferometry implementing spectroscopy and refractometry of a sample. Broadband time–frequency entangled photon pairs are used as the quantum light probe, and phase modulation with lock‐in detection is used to reduce the sampling requirements needed to characterize fully the temporal interference pattern.